2x over 15
If you mean as an equation in the form of 8x+4 = 68 then x equals 8
6xy/16y = 3x/8 (as long as y≠0) = 3/8x
The answer is nine. Seriously. Here is my work if you don't believe me: 68=8x+23+4x-7x 68=8x-7x+23+4x 68=x+23+4x 68=x+4x+23 68=5x+23 68-23=5x 45=5x x=45/5 x=9
It is an algebraic expression in the form of: 8x+10
ax+by=c --- standard form and slope intercept form is y=mx+b,, so for example: 8x+4y=16 ----this in its standard form so if we change it to slope intercept form, we transpose 8x beside 16.. there fore, the result is 4y=-8x+16. .however.. in slope intercept form,, the variable y should not have any coeffiecient.. so we should dived 4y, -8x and 16 by 4,, therefore the result is y=-2x+4.. so the slope intercept form of 8x+4y=16 is y=-2x+4
There is a formula for the "difference of squares." In this case, the answer is (8x + 7)(8x - 7)
slope intercept form y = mx + b 8x-6y = 48 -6y = -8x + 48 y = (-4/3)x + 8
18 + 8x + x = = 18 + 9x = 9(2 + x) which is the factored form of the expression.
8x - 7y + 2 = 0 The slope-intercept form is NOT the standard form. The above form is easily generalised to 3 (or more) dimensions, not so with the slope-intercept form.
This equals 5.333.
X2 - 8X + 15 = (X - 3)(X - 5)
The simplest way is to rewrite the equation in the standard for: y = mx + c. Then the slope is m. 8x - 7y = 56 7y = 8x - 56 y = 8/7 * x - 8 So the slope is 8/7
8x + 3y = 248x - 8x + 3y = -8x + 243y = - 8x + 243y/3 = (- 8x + 24)/3y = -8x/3 + 24/3y = (-8/3)x + 8 this is the slope-intercept form of the equation of the line, y = mx + b, where the slope m is -8/3 and the y-intercept b is 8.
Assuming the 2 is meant to be a square this is the form: x2 - 3x2 = -2x2 + 8x + 5
8x-5y = -40 -5y = -8x-40 y = 1.6x+8 which is now in slope intercept form
= 2x + 4